The effect of inspiratory muscle training on fatigue and dyspnea in patients with heart failure: A randomized, controlled trial. Issue 2 (19th August 2019) - Hossein Pour, Amir Hossein; Gholami, Mohammad; Saki, Mandana; Birjandi, Mehdi
Abstract: Aim: Fatigue and dyspnea are debilitating symptoms in patients with heart failure (HF). The purpose of this study was to evaluate the effects of inspiratory muscle training (IMT) on dyspnea, fatigue and the New York Heart Association (NYHA) functional classification in patients with HF. Methods: In this prospective, randomized, controlled trial, 84 patients with HF (NYHA classes II‐III/IV) with a mean age of 56.62 ± 9.56 years were randomly assigned to a 6‐week IMT ( n = 42) or a sham IMT ( n = 42) program. The IMT was performed at 40% of the maximal inspiratory pressure (MIP) in the IMT group and at 10% in the sham group. The main outcomes were assessed at baseline and after the intervention and included dyspnea severity scale (Modified Medical Research Council [MMRC], Fatigue Severity Scale [FSS] and the NYHA functional classification (based on the presenting symptoms). Results: The between‐group analysis showed significant improvements in dyspnea, fatigue and the NYHA functional classification in the IMT group compared to the sham group ( P < .05). The within‐group analysis showed significant improvements in dyspnea (from 2.63 ± 0.79 to 1.38 ± 0.66, P < .001), fatigue (from 43.36 ± 8.5 to 28.95 ± 9.11, P < .001) and the NYHA functional classification (from 2.73 ± 0.5 to 2.1 ± 0.6, P = .001) in the IMT group, while fatigue and dyspnea increased significantly in the sham group. Conclusions: The 6‐week home‐based IMT was found to be an effective and safe tool for reducing dyspnea and fatigue and improving the NYHA functional classification.